Glimpse on shigellosis from endemic Bangladesh: decades of observation with urban-rural differentials - Barua, Dipesh Kumar; Das, Sumon Kumar; Faruque, Abu Syed Golam; Sarker, Mohammad Habibur Rahman; Das, Jui; Ahmed, Shahnawaz; Malek, Mohammad Abdul; Shahunja, KM; Chisti, Mohammod Jobayer (Bangladesh Critical Care Journal, 2016)
The Diarrhoeal Disease Surveillence System of icddr,b noted increasing proportion of Shigella sonnei and Shigella flexneri at urban Dhaka and rural Matlab from 2000 to 2013. Shigella sonnei appeared as emerging serogroup during 2009-13 compared to 2000-04 among individuals aged ? 60 years both in Dhaka and Matlab, while Shigella boydii and Shigella flexneri showed remarkable increase with 400% and 100% respectively in Dhaka, and a moderate increase (55%) both Shigella boydii and Shigella flexneri in Matlab. However, decreased trend of all the Shigella species in both the sites except Shigella dysenteriae in Dhaka was found among under-5 children. Individuals from higher socio-economic status such as those having a monthly family income of >100 USD had protective role against shigellosis in Dhaka during 2009-13. Shigella species and host factors are responsible for changing trend as well as predictors of shigellosis. Bangladesh Crit Care J September 2016; 4 (2): 105-109